Cognitive and Affective Symptoms Experienced by Cancer Patients Receiving High-Dose Intravenous Interleukin 2 Therapy: An Integrative Literature Review. Issue 5 (September 2016) - Mann, Tara K.; Dail, Robin B.; Bailey, Donald E.
Abstract : Background: Alterations in cognitive/affective functioning are among the most challenging adverse effects experienced by 80% of patients with metastatic melanoma and metastatic renal cell carcinoma undergoing high-dose interleukin 2 (IL-2) therapy. Objective: The purpose of this literature review is to describe what is known about IL-2–induced cognitive/affective symptoms, their prevalence, and level of severity and synthesize findings to determine areas for future research to address symptom management challenges. This review describes the IL-2 patient experience and the pathophysiology leading to these changes. Methods: An online electronic search using PubMed was performed to identify relevant literature published between 1992 and 2015. Of the original 113 articles, information was extracted from 9 articles regarding cognitive symptoms, affective symptoms, sample size, research design, reliability, and validity. Results: Our review suggests that the trajectories, breadth, and depth of cognitive/affective symptoms have yet to be described. Despite intervention studies designed to address the psychosocial complications of IL-2, an understanding of the level of altered cognitive/affective symptoms experienced by IL-2 patients remains unclear. Conclusion: Our literature review reveals a lack of standardization when assessing, reporting, and managing cognitive/affective symptoms. Patients/family members have reported cognitive/affective symptoms to be the most alarming and difficult symptoms, yet these symptoms are not adequately screened for, and patients were not informed about potential changes. Implications for Practice: Assessing patients for cognitive/affective alterations is important to reduce anxiety while improving outcomes. Education about the illness trajectory (what to expect during/after treatment) can help care partners/patients set realistic shared expectations and increase coping.